Proton-conducting Solid-state Electrolytes for Fuel Cells Operating at Reduced Temperatures - Wang, Zehua (Curtin University, 2024)
Designing efficient and durable solid-state electrolytes is crucial for fuel cells operating at reduced temperatures (200-600°C). This thesis explores improvements in polymer electrolyte membranes and perovskite electrolytes to address key challenges. The research evaluates and analyses the performance and reaction mechanism of in-situ formed phosphate/phosphoric acid/polybenzimidazole membranes, and proposes new theories on the improved sinterability of BaCe(Zr)O3 perovskites. These advancements provide valuable insights for developing more robust and high-performing electrolytes for future fuel cell applications.